Hubungan Genotipe DNA Human Papillomavirus (HPV) terhadap Respons Terapi Radiasi pada Karsinoma Sel Skuamosa Serviks - CUT ADEYA ADELLA (National Cancer Center - Dharmais Cancer Hospital, 2014)
The importance of human papilloma virus (HPV) infection in the outcome of cervical cancer after radiotherapy remains unknown. Our study explored whether the HPV status of tumors is associated with the outcome of radiotherapy in patients with cervical cancer. The biopsy cervix samples taken from 31 patients with squamous cell carcinoma cervix (Stage IIB-IIIB) that met in the inclusion criteria. The HPV were genotyping examination was conducted twice before and 3 month after radiation therapy. The subjects treated by radiation therapy according to standard procedures. After undergone complete radiation, response of radiation therapy was conducted by clinical assessment and repeat HPV genotyping test. A total of 31 patients had HPV-positive tumors in 83.37% (27 cases) of patients, with the details of a single infection of 75% and 9:37% multiple infections. Based on the type of HPV type 16 was obtained (43.74%), type 18 (18.64%). Persistent infection with HPV after radiation encountered by 34.61%. Complete clinical response observed in the single infection group number of 100%, while in the group of multiple infections by 33.3% (p = 0.115). While HPV infection settled with a complete clinical response by 32% (p = 0.346). There were no statistically relationships between clinical complete response with single or multiple HPV infection (p = 0.115). There were no statistically relationship between persistent HPV infection with complete clinical response. (p = 0.346)